2016
DOI: 10.1177/1524838015585316
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Traumatic Situations in the Face of Ongoing Political Violence

Abstract: This article presents a literature review of the concept of continuous traumatic situations (CTS), which relates to residents living in ongoing situations of political violence and national security threats. The first aim of this review is to narrow the gap regarding knowledge about the concept of CTS by presenting findings from studies that have assessed the effects of CTS on civilian populations. The second aim is to describe CTS in a way that highlights the differences and similarities between posttraumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 65 publications
1
48
0
Order By: Relevance
“…Unceasing exposure to trauma leads to a substantial degradation of individuals’ psychological, social, and economic resources (e.g., Hobfoll et al, 2008 ), and this degradation could in turn limit one's capacity to handle a new stressor. Furthermore, the reality of ongoing threat/danger not only deprives one of the opportunity to experience recovery in a safe and protected environment ( Lahad and Leykin, 2010 ; Nuttman-Shwartz and Shoval-Zuckerman, 2016 ), but also repeatedly confirms a sense of threat and helplessness. As such, the negative effects of the ongoing trauma and subsequent PTSD symptoms on coping with an additional stressor might be particularly potent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unceasing exposure to trauma leads to a substantial degradation of individuals’ psychological, social, and economic resources (e.g., Hobfoll et al, 2008 ), and this degradation could in turn limit one's capacity to handle a new stressor. Furthermore, the reality of ongoing threat/danger not only deprives one of the opportunity to experience recovery in a safe and protected environment ( Lahad and Leykin, 2010 ; Nuttman-Shwartz and Shoval-Zuckerman, 2016 ), but also repeatedly confirms a sense of threat and helplessness. As such, the negative effects of the ongoing trauma and subsequent PTSD symptoms on coping with an additional stressor might be particularly potent.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of previous traumatic events (that are not ongoing) might benefit from evidence-based treatments such as trauma-focused cognitive behavior therapy (TF-CBT; Hobfoll et al, 2008 ), which could be provided online and would tap specific challenges that survivors might experience when dealing with the pandemic. Individuals exposed to CTS, on the other hand, need specific clinical interventions that are tailored to the particular struggles that they face ( Nuttman-Shwartz and Shoval-Zuckerman, 2016 ). Treatment for individuals exposed to CTS should be directed towards managing anxiety and physical symptoms, and the acquisition of day-to-day coping skills, and not on a reprocessing of the trauma, as is generally done when treating survivors of traumatic events that are not ongoing ( Diamond et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms must last more than one month to qualify for a clinical diagnosis of PTSD (American Psychiatric Association, 2013). Chronic exposure to political violence is different than acute exposure in the nature of its accumulative effects and is associated with increased PTSD (Buka, Stichick, Birdthistle, & Earls, 2001; Nuttman-Shwartz & Shoval-Zuckerman, 2015). …”
mentioning
confidence: 99%
“…Moreover, because people living under conditions of ongoing traumatic stress are currently in danger, their responses to the emergency situation, including avoidance and hyperarousal, can be understood as natural, protective and adaptive (Nuttman-Shwartz and Shoval-Zukerman, 2015). In those situations, trauma workers (including social workers) have reported that they temporarily shift their attention to the emergency.…”
Section: Introductionmentioning
confidence: 99%